ANALISIS EVALUASI PEMBELAJARAN MATEMATIKA SECARA DARING - Mila Fatmawati; Mohammad Rif’at; Dona Fitriawan Sunarti (Jurnal Numeracy, 2023)
The background of this research is the use of online evaluation of mathematics learning and cognitive level in end-of-semester assessment questions (PAS) based on the revised Bloom's Taxonomy. The purpose is to find out what types of evaluation tests are used during online learning and the cognitive level contained in the questions. The method used in this research is quantitative research with data collection tools including end-of-semester assessment questions (PAS) for class VIII mathematics, questionnaires, and interview guidelines. Mathematics teacher and 29 students of class VIII are the subjects of this research. From the analysis carried out, the cognitive levels contained in the mathematics PAS questions are; level 1 includes knowing & understanding (C1 & C2), level 2 applying (C3), and level 3 consisting of analyzing (C4), and the types of evaluation tests used are assignments, daily assessments, post-tests, midterm assessments, and end of semester assessment.